Multi-User and Real-Time Flexible Remote Laboratory Architecture for Collaborative and Cooperative Pedagogical Scenarios - Farah, Said; Abdelhalim, Abdelhalim; Guillaume, Neveux; Barataud, Denis; Andrieu, Guillaume; Fredon, Thomas (International Journal of Online and Biomedical Engineering (iJOE), 2016)
An advanced multi-user and realtime INTernational-REmote-LABoratory (INT-RE-LAB) architecture is presented in this paper. The INT-RE-LAB is developed and localized in four different host universities. The software part is based on the use of a free license server Node.js written in JavaScript. It offers lightweight Html/JavaScript clients. The integration of socket.io module enables a real-time operation mode of this Client/Server communication. Associated with hardware architecture, collaborative remote manipulation of resources is enabling in the same way as a chat communication used in Internet. Each remote action performed by one user is instantaneously visible in other users’web interfaces. The hardware part includes a mini-computer that executes node.js server and hosts MySQL. Mini-computer “Pcduino” directly controls specifically developed relays circuit. It offers the required flexibility and reusability for current remote laboratories. Different redundant remote practical works integrate the INT-RE-LAB have been developed for the new EOLES “Electronics and Optic e-Learning for Embedded Systems” bachelor.